Internalisasi Nilai Tazkiyatun Nafs melalui Pembiasaan Ritual Keagamaan dalam Pembentukan Kecerdasan Spiritual - Citra Oktavia Handayani; Saiful Bahri (Universitas Islam Darud Da'wah Wal-Irsyad A.G.H. Abdurrahman Ambo Dalle, 2026)
This study is motivated by the importance of developing students’ spiritual intelligence amid rapid technological advancement and increasingly complex moral challenges. Many students possess adequate academic abilities; however, they often face difficulties in self-control, worship discipline, and the internalisation of Islamic values in daily life. Therefore, education should not only emphasise cognitive achievement but also foster spiritual development through Islamic educational approaches. One such approach is tazkiyatun nafs, which refers to the process of self-purification through the stages of takhalli, tahalli, and tajalli. This study aims to describe the implementation of tazkiyatun nafs in developing students’ spiritual intelligence at SMPIT Al-Utsmaniyah. A qualitative approach with a descriptive analytical method was employed. Data were collected through observation, interviews, and documentation involving the headmaster, teachers, students, and parents as informants. Data were analysed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings revealed that tazkiyatun nafs was implemented through various spiritual habituation programmes, including congregational prayers, dhikr, Qur’anic muroja’ah, kultum, moral development activities, and teachers’ role modelling. These findings contribute to the development of Islamic education, particularly in strengthening character and spiritual development of students through the tazkiyatun nafs approach in the school environment. The implementation contributed significantly to the development of students’ spiritual intelligence, self-discipline, worship awareness, emotional control, and religious character in daily life.